Answer:
24
Step-by-step explanation:
6+6 =12
12+6 = 18
18+6 = 24
Answer:
Step-by-step explanation:
(47+1)/(3-6) = 48/-3 = -16
y + 1 = -16(x - 6)
y + 1 = -16x + 96
y = -16x + 95
D) EFGH moved onto E'F'G'H after rotating 180 counterclockwise around the origin and the reflecting across the y-axis.
<h3>How to carry out transformations?</h3>
From online resources gotten about this question, for quadrilateral EFGH and quadrilateral E'F'G'H to be congruent, what we must do first is to rotate 180° counterclockwise around the origin and then move EFGH onto E'F'G'H'.
The last step to get this proof of congruency is to reflect across the y-axis.
Read more about transformations at; brainly.com/question/4289712
#SPJ1
Answer:
Huh I am confused
Step-by-step explanation:
Do you need help with anything